THE IMPACT OF OCEANOGRAPHIC PARAMETERS CHANGES ON THE DISTRIBUTION AND ABUNDANCE OF SKIPJACK TUNA Katsuwonus pelamis IN MAKASSAR STRAIT - Zabhika Dinda Istnaeni; Mukti Zainuddin (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
This study aimed to identify the changes of oceanographic parameters and to analyze the effects of the parameter changes on the distribution and abundance of skipjack tuna captured by purse seine fishing gear operated in Coastal Waters of Makassar Strait. This study collected fishing and field oceanographic data from May to October 2017. A survey method was used to obtain primary data (skipjack catch per unit effort/CPUE) and secondary data including sea surface temperature (SST) and Chl-a level 3 with a monthly temporal and spatial resolution of 4 km from 2007-2017, interview, and study literature. The data were processed by using SeaDAS and ArcGIS software packages and were analyzed by anomalies, standard deviation, and Generalized Additive Models (GAMs) analyses. The results showed there were anomalies for both SST and Chl-a near study area reflecting the significant changes in the oceanographic conditions. The changes for both SST and Chl-a were 1.5ºC and -0.97 mg.m-3 respectively. This study suggests that the Chl-a parameter has more significant effects on skipjack tuna distribution and CPUE than SST. Understanding of the areas of the oceanographic changes strongly supports the available habitat for the fishing operation and conservation